Análisis de la demanda para la creación de una empresa de servicio turístico en chiva en el cantón Montalvo - Verdezoto Aguila, Dennis Gabriel (2020)
This case study was carried out in Montalvo a canton of the Los Ríos Province, a tourist destination that has relevant natural resources. The main objective of the research is to determine the degree of acceptance by the demand for the creation of a tourist service company in chiva in Montalvo. For the purposes of the study, the type of qualitative, descriptive and explanatory research was used, in addition to deductive, exploratory, bibliographic and field methods, through the convenience sampling technique. The results of this research provide data for the analysis of the demand for tourist transport in this area of the country, which serves as an input for public and private tourism planning. What would contribute to the creation of new ventures, investment and local tourism development. The present study established that the degree of acceptance by the demand of the tourist service in chiva in Montalvo is high, mostly hikers who travel in groups of two to four people on weekends.